School Board Leadership: Best Practices - Brian T. Sims (The Advocate, 2017)
The purpose of this article is to identify school board best practices in K-12 education. Research suggests that school boards must continue to be actively involved in the governance of local policies and practices regardless of the size of the school district. In addition to monitoring progress and taking corrective action when school goals are not met, school boards must work collaboratively to create a vision, remain committed to the goals they set, and continue to use data to make educational decisions.